Pelatihan Batik Shibori Pada Kelompok Belajar Binaan Karang Taruna “Rinjani Asri” - Siti Rabiatul Adawiyah; Intan Kusuma Wardani; Nofisulastri Nofisulastri; Fitri Astutik; Muhamad Sarifuddin (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
Based on the results of the study, shibori batik can improve children's fine and gross motor skills because it’s interesting and not boring and has the goal of training the flexibility of the finger muscles, avoiding boredom, and as an alternative for psychological health first aid for disaster survivors, especially during the pandemic. covid 19. One of the phenomena of the impact of the pandemic, problems were found in the "Rinjani Asri" youth group in the Rinjani Asri housing area, Jatisela village, Gunungsari district, West Lombok district, such as the lack of socialization of the existence of youth organizations and their role during the pandemic. The target of community service were 13 people which 9 members of the study group and 4 members of the youth organization "Rinjani Asri". The implementation method consists of five stages including communication, observation and legality, strategy, execution, and evaluation of activities. Based on the evaluation of the activity responses, its were found that 100% understood shibori batik and were able to participate in training demonstrations, 78% were confident in creativity (binding/color selection/fabric dyeing techniques), and 100% were categorized as useful. In addition, the level of enthusiasm of the participants in the category were quite high (discipline and punctuality, the number of products produced), and during the procession of the participants' activities no one was seen using a gadget/cell phone or playing games.